ANALYSIS OF THE EFFECT OF TAX SANCTIONS AND EASE OF REPORTING IMPLEMENTATION ON COMPLIANCE IN TAXPAYERS - Liona Agustriana; Murni; Mahdalena; Asyifa; Ajirna (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Taxpayer compliance is a situation where taxpayers comply with all applicable tax regulations. Taxpayer compliance is a very important factor in achieving successful tax revenue. This study aims to determine how much influence tax sanctions and ease of reporting implementation have on compliance in doing taxpayers in Bireuen Regency. The strategy used in this research is a quantitative descriptive research strategy. The method used in this research is purposive sampling method. The sample in this study amounted to 400 respondents with different age groups and types of work. The data collection technique used was to conduct several interviews, observations and questionnaires. The results showed that there was a significant effect of tax sanctions on taxpayer compliance in carrying out their tax obligations. The ease of application of reporting that affects compliance in doing taxpayers. Then there is an effect of tax sanctions and ease of application of reporting on compliance in doing taxpayers simultaneously.